Fertility and the influence of women's industries - Nicola Hülskamp (Luxembourg Income Study (LIS), 2006)
The influence of the working life of women on their number of children has been widely discussed among demographers. Already in 1979, Butz and Ward demonstrated a negative correlation between the fertility and workforce participation of women in the US. Since then many researchers have gathered evidence of a negative correlation, even though the concrete impact of the different factors on each other remains unclear. Whereas there are no indications of a correlation between the employment and fertility of men, researchers believed that women with higher wages had fewer children than women with lower wages. Recent studies, however, indicate the opposite. They show a positive correlation between fertility and labour force participation of women for some countries and even present evidence that women with higher wages have more children than women with lower wages. Therefore, it becomes more and more apparent that the correlation between women's fertility and employment is not a constant but that the institutional context of the state has a major influence on the fertility decision of women. Moreover, institutional factors also have an impact on the occupational arrangement mothers choose. Other factors which play into the fertility decision are the professional training of the mother, the attitude of the surrounding society on the compatibility of motherhood and work or the role of the father. The institutional arrangements of childcare or job conditions also seem to play a major role in the decision for or against a child. It has been empirically proven, that women who can determine their working hours freely and whose careers depend very little on their job performance, have their children earlier and return to their work place sooner than other women. Studies finding a positive correlation between women's employment and fertility in Sweden point out that most Swedish mothers are employed in the public sector (Hoem, 2000; Hoem / Hoem, 1989). Specific studies of the correlation between working in a specific industry and the fertility of women are hard to find, however. This study aims at making first steps to fill this gap.
Keywords: 330; Fertilität; Weibliche Arbeitskräfte; Beruf; USA; Kanada; Großbritannien; Deutschland